Water-gas shift reaction catalyzed by redox enzymes on conducting graphite platelets. - Lazarus, O; Woolerton, T; Parkin, A; Lukey, M; Reisner, E; Seravalli, J; Pierce, E; Ragsdale, S; Sargent, F; Armstrong, F (2009)
The water-gas shift (WGS) reaction (CO + H(2)O <==> CO(2) + H(2)) is of major industrial significance in the production of H(2) from hydrocarbon sources. High temperatures are required, typically in excess of 200 degrees C, using d-metal catalysts on oxide supports. In our study the WGS process is separated into two half-cell electrochemical reactions (H(+) reduction and CO oxidation), catalyzed by enzymes attached to a conducting particle. The H(+) reduction reaction is catalyzed by a hydrogenase, Hyd-2, from Escherichia coli, and CO oxidation is catalyzed by a carbon monoxide dehydrogenase (CODH I) from Carboxydothermus hydrogenoformans. This results in a highly efficient heterogeneous catalyst with a turnover frequency, at 30 degrees C, of at least 2.5 s(-1) per minimum functional unit (a CODH/Hyd-2 pair) which is comparable to conventional high-temperature catalysts.